Fatal Hemoptysis Secondary To Fibro-Inflammatory Igg4-Related Lung Disease: A Case Report (2016)
IgG4-related disease (IgGe-RD) is a fibro-inflammatory condition that affects nearly every organ; it was initially describe in the pancreas, by lesions with plasma cell infiltration with IgG4+. It presents a dense lymphoplasmocytic infiltrate, occasionally pseudotumoral, with fibrotic stroma with a storiform pattern and obliterative phlebitis, the lung representation was characterized in 2011, two thirds of the patients had increased IgG4 levels, there is a response to steroids in early stages of the disease.